1999
DOI: 10.1177/009102609902800305
|View full text |Cite
|
Sign up to set email alerts
|

Managing Career Plateauing in the Quebec Public Sector

Abstract: Many events in recent decacies have made promotion opportunities increasingly scarce, thus significantly changing the career prospects of a large number of individ uals. Feelings of career failure can have negative consequences for both individuals and organizations. Based on a survey of 192 managers and professionals in the Quebec public sector, our results indicate that the absence or inadequacy of practices linked to career planning, development, and support, as well as the lack of opportu nities to play ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 1 publication
4
35
2
2
Order By: Relevance
“…In terms of OCBs, the finding that job content plateaus were negatively related to individually-focused forms of OCBs is consistent with research revealing a negative relationship between plateauing and job performance (Allen, et al, 1998;Ettington, 1998;Lemire et al, 1999). Interestingly, hierarchical plateaus were not significantly related to OCBs.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In terms of OCBs, the finding that job content plateaus were negatively related to individually-focused forms of OCBs is consistent with research revealing a negative relationship between plateauing and job performance (Allen, et al, 1998;Ettington, 1998;Lemire et al, 1999). Interestingly, hierarchical plateaus were not significantly related to OCBs.…”
Section: Discussionsupporting
confidence: 83%
“…Individuals who engage in OCBs go above and beyond the formal requirements of their jobs to help the organization (Podsakoff, MacKenzie, Paine, and Bachrach, 2000). OCBs have not been examined to date in relation to plateauing but the negative relationships observed between plateaus and job performance (Allen, et al, 1998;Ettington, 1998;Lemire et al, 1999) indicates employees may reduce their job performance when they feel stifled in their careers. It seems plausible that if plateaued employees are willing to reduce effort for their mandatory tasks at work, they may also be less willing to engage in extra-role behaviors such as OCBs.…”
Section: Stress and Ocbs Among Plateaued Employeesmentioning
confidence: 99%
“…Previous literature has documented that plateau employees are more likely to report low organizational identification, high turnover intention [27], low work satisfaction, low effective, and low continuous commitment [17], and less involvement in their work [10]. Hobfoll, Vinokur, Pierce, & Lewandowski-Romps [8] suggested that career plateauing is a source of stress for employees, thus, reducing their job involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Além disso, mostra como a falta de integração entre as necessidades individuais e as recompensas oferecidas pode levar à percepção que a carreira estagnou, situação associada a um comportamento de resistência à mudança, à baixa inovação, à valorização excessiva de recompensas extrínsecas (salários e benefícios), à homofilia e à busca de segurança acima de tudo (FELDMAN;WEITZ, 1988: KATZ, 1980LEMIRE;SABA;GAGNON, 1999; VAN DAM, 2004).…”
unclassified